English Literary Studies: An Islamic Perspective and Method (American Journal of Islam and Society, 2014)
On January 15, 2014, Md. Mahmudul Hasan, assistant professor in the Departmentof English Language and Literature at the International Islamic UniversityMalaysia, addressed an audience at the IIIT headquarters in Herndon,VA. He spoke on how Muslims have tended to associate English studies withwestern value systems, secularism, and anti-Islamic practices.He opened his talk with some background information. He was educatedat a madrassa and then chose to study western (English) literature, much tohis father’s disappointment – he firmly believed that his son, whom he hadalways envisaged as an Islamic scholar, would come out of the university asa secularist, an atheist, or an agnostic. Although this may not be the case today,at his father’s time people could actually see their university-enrolled childrenundergo some changes or adopt the various western lifestyles uncritically atthe expense of their traditional Islamic upbringing.Reflecting further on the context that had given rise to this attitude, Hasanpointed out the tendency at that time, and based solidly upon the Subcontinent’scolonial experience, to associate English literature studies with bothcolonialism and western Christendom. In response to this, contemporaryscholars of postcolonial studies employ the twin strategies of abrogation andappropriation to dismantle the original intent behind introducing English literarystudies and, simultaneously, to create platforms of self-assertion and resistance.Those who support the Islamization of English literary studiespropose a similar approach to English literature in order to counterbalance theun-Islamic cultural influences as well as to present the Islamic worldviews inrelation to the life-worlds that these literary texts are reputed to promote.He said that many Muslims find it difficult to reconcile “Islam” and “Englishliterature,” for how can there be any relationship between them? This isnot as illogical as it may seem, however, for the British introduced Englishliterature into the Subcontinent long before they introduced it into the UnitedKingdom itself. It was offered in the former in 1830, but only ninety yearslater in the latter. In fact, according to Hasan, the subject itself has a colonialbackground, for it, along with Christian missionary activity, was designed to ...